Advanced Materials Based on Polymers and Ionic Liquids. Issue 4 (19th September 2017) - Kitazawa, Yuzo; Ueno, Kazuhide; Watanabe, Masayoshi
Abstract: Ionic liquids (ILs) are ambient temperature molten salts, which have attracted considerable attention owing to their unique properties. In this contribution, we review advanced materials composed of ILs and polymers for the basis of a new design protocol to fabricate novel materials. As electrolytes for electrochemical devices, cross‐linked polymers containing ILs (ion gels) are endowed with functional properties inherited from ILs and mechanical consistency derived from polymers. To create such materials, micro‐phase separation of block copolymers and colloidal arrays in the ILs are utilized. Based on the molecular design of task‐specific ILs, the resultant ion gels are applicable as electrolytes for actuator, fuel cell, and secondary battery applications. Thermo‐ and photo‐responsive polymers in ILs are also highlighted, whereby such stimuli elicit changes in the solubility of the self‐assembly of block copolymers and colloidal arrays in the ILs. Further, thermo‐ and photo‐reversible changes in the self‐assembled structure can be exploited to demonstrate sol‐gel transitions and fabricate photo‐healable materials. Abstract : Soft materials consisting of ionic liquids and polymers (ion gels) possess functional properties inherited from ILs and mechanical consistency derived from polymers. To create such materials, micro‐phase separation of block copolymers in the ILs are utilized. Based on the molecular design of the polymer and the ILs, the ion gels are applicable for actuator, fuel cell, and secondary battery applications. Thermo‐ and photo‐responsive polymers in ILs can be exploited to demonstrate stimuli‐triggered sol‐gel transitions and fabricate photo‐healable materials.